1990
DOI: 10.1210/endo-126-4-2164
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-I Analogs: Effects on Insulin Secretion and Adenosine 3′,5′-Monophosphate Formation*

Abstract: Glucagon-like peptide 1-(7-37) [GLP-I-(7-37)] is a 31-amino acid hormone which may have an important role in the regulation of insulin secretion, It is processed from preproglucagon and found in the pancreas, brain, and, in highest quantity, intestine. In previous studies we found that GLP-I-(7-37) is a potent insulin secretagogue, and its effect was indistinguishable from that of GLP-I-(7-36) amide at concentrations of 10(-11) M. Herein we report insulinotropic effects of additional GLP-I analogs. GLP-I-(7-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 18 publications
3
60
1
Order By: Relevance
“…DISCUSSION We propose that MTX activates the same non-selective cation current as stimulation with the peptide hormones GLP-1 and PACAP (6,7,22). These hormones couple through GTPbinding proteins (G-proteins) to activate adenylyl cyclase and elevate intracellular cAMP in ␤-cells (3)(4)(5), and cAMP analogs can also activate these non-selective cation currents. However, activation of G-proteins, by dialysis of cells with KF, KF ϩ AlF 3 , or GTP␥S (compounds that stimulate G-protein mediated activation of non-selective cation currents in epithelial cells (33) and activate K ϩ ATP channels in RINm5F and HIT-T15 insulinoma cells (34,35)), neither activated nor inhibited the MTX-sensitive current.…”
Section: Fig 5 Activation Of the Mtx-sensitive Current Is Dependentmentioning
confidence: 91%
See 3 more Smart Citations
“…DISCUSSION We propose that MTX activates the same non-selective cation current as stimulation with the peptide hormones GLP-1 and PACAP (6,7,22). These hormones couple through GTPbinding proteins (G-proteins) to activate adenylyl cyclase and elevate intracellular cAMP in ␤-cells (3)(4)(5), and cAMP analogs can also activate these non-selective cation currents. However, activation of G-proteins, by dialysis of cells with KF, KF ϩ AlF 3 , or GTP␥S (compounds that stimulate G-protein mediated activation of non-selective cation currents in epithelial cells (33) and activate K ϩ ATP channels in RINm5F and HIT-T15 insulinoma cells (34,35)), neither activated nor inhibited the MTX-sensitive current.…”
Section: Fig 5 Activation Of the Mtx-sensitive Current Is Dependentmentioning
confidence: 91%
“…The consensus model of glucose-stimulated insulin secretion is that closure of ATP-sensitive K ϩ channels (K [3][4][5]. One mechanism underlying this increased responsiveness is the enhanced closure of K ϩ ATP channels (2).…”
Section: ؉mentioning
confidence: 99%
See 2 more Smart Citations
“…This was confirmed with proteolytic digests using either chymotrypsin or trypsin. According to other studies, the N-terminal region may be important for biological activity through a mechanism not involving receptor binding (Gefel et al, 1990;Mommsen & Moon, 1990;Plisetskaya, 1990). Some studies have suggested that the N-terminal region of the hormone forms an aliphatic alpha-helix, which inserts into the lipid bilayer (Oomen & Kaplan, 1990).…”
Section: Discussionmentioning
confidence: 96%